TRANSSHIPMENT ANALYSIS WITH LINGO SOFTWARE AT PT.SBT - Kurnia, Niken Septiani (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Application of the transhipment model in transportation is often found in the business world, whether for consolidation or dividing the product into several parts until it is finally sent to its destination. This condition sometimes causes companies to incur significant costs for transportation and product lead time to reach consumers that is longer so that it affects the customer service level, when in fact the company wants a good customer service level as well as maximum profits with minimum costs. PT. SBT which is a company engaged in the distribution of building goods is also inseparable from transportation activities that implement a transhipment system with ownership of 3 warehouses as a transit point, where these three warehouses have different locations so that further research is needed whether there is a third The warehouse transportation costs incurred are optimal or not. The study was conducted using secondary data from previous research with the aim of comparing the results of the methods used in previous studies with the results of this study, so as to provide the best input for companies in transportation aspects in order to achieve company goals. The approach used in solving this transhipment problem is using Lingo software which, of course, hopes to provide optimal results. The results showed a decrease in total transportation costs, which was originally Rp 3,275,000 to Rp 1,413,000 with a difference in fees of Rp 1,862,000 or by 56.85%.